2021
DOI: 10.3168/jds.2021-20291
|View full text |Cite|
|
Sign up to set email alerts
|

Radioprotective effect of radiation-induced Lactococcus lactis cell-free extract against 60Coγ injury in mice

Abstract: Ionizing radiation (IR) is widely used in the diagnosis and treatment of various cancers. However, IR can cause damage to human health by producing reactive oxygen species. Lactococcus lactis is a type of microorganism that is beneficial to human health and has a strong antioxidant capacity. In this study, the protective effect of normal and IR-induced L. lactis IL1403 cell-free extracts (CFE and IR-CFE, respectively) against oxidative damage in vitro and the radioprotective effect of IR-CFE in vivo was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Ionizing radiation could produce excessive free radicals, which damage immune organs and cells, thus causing the abnormal immune function of the body. Previous studies had reported that the mechanism of radiation‐induced liver injury was related to immunomodulatory effects (Kang et al, 2019; Suo et al, 2021). It was shown in Figure 6a–c that PCPP‐1A exhibited good immunomodulatory activity in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Ionizing radiation could produce excessive free radicals, which damage immune organs and cells, thus causing the abnormal immune function of the body. Previous studies had reported that the mechanism of radiation‐induced liver injury was related to immunomodulatory effects (Kang et al, 2019; Suo et al, 2021). It was shown in Figure 6a–c that PCPP‐1A exhibited good immunomodulatory activity in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…The use of radioprotectors could improve the therapeutic gain of radiation therapy [ 8 ]. Various radioprotectors have been introduced that can be very effective and helpful in mitigating the side effects of IR [ [9] , [10] , [11] , [12] , [13] , [14] ]. Flavonoids are a group of natural polyphenolic compounds that have been identified in many plants in different species and can have radiation protection properties [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%